PELATIHAN DIGITAL MARKETING SEBAGAI UPAYA PENGEMBANGAN STRATEGI PEMASARAN PRODUK UMKM BATIK DI KELURAHAN GEDOG KOTA BLITAR - Febrialdy Yogapratama Febri; Dianur Permatasari; Isabella Intan Kurniafitra; Wulansari Islamiah (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2022)
In this modern era, digital marketing has become a mainstay or prima donna in the world of marketing. However, not all MSMEs have the ability to change their marketing patterns to digital marketing. Low educational background and lack of knowledge about the internet, development, and technology are the factors that caused the use of digital marketing in MSMEs to be not optimal. Based on the previous statement, It is the researcher's goal in determining activity plan in the form of a training program to help MSMEs exploit digitalization, a program that is being mutual concern from the academic sector, the business sector, and support from the government. According to these problems, digital marketing training programs for business doers are very suitable. Therefore, it requires planning and the steps that must be passed. It contains 1) planning, 2) organizing, and 3) actuating. The training explained clearly the concept or definition, as well as the forms of digital marketing. In addition, it also explained about the forms of digital marketing. The advantages of digital marketing include the Internet being one of the centres of online digital marketing, being able to easily disseminate content via the internet, business organizations being able to see real-time marketing activities carried out, and the distribution process being fast. The weakness of digital marketing itself is that it is difficult to implement without knowledge and experience. Regarding marketing strategy, digital marketing goes through several stages which are, 1) understanding the target market, 2) analysing the competitors, 3) prioritising digital tactics and channels, 4) maximising channel potential, 5) measuring results and 6) analysing effectiveness. The digital marketing training conducted by the Wira Desa Team is very helpful for improving the capability of human resources, especially for business doers in scope of digital marketing.